Semantic challenges to realism : Dummett and Putnam - Gardiner, Mark Q. (Mark Quentin), 1963- (Toronto, Ont. : University of Toronto Press, 2000)
Although many philosophers espouse anti-realism, the only sustained arguments for the position are due to Michael Dummett and Hilary Putnam. Gardiner's unpretentious style and lucid organization make sense of Dummett's and Putnam's discourse.
K -- L -- M -- N -- P -- Q -- R -- S -- T -- U -- V -- W -- Y.
Includes bibliographical references (pages 253-261) and index.
Print version record.
English.
JSTOR
Keywords: Dummett, Michael, -- 1925-2011.; Putnam, Hilary; Dummett, Michael, -- 1925-2011; Putnam, Hilary; Dummett, Michael A. E; Putnam, Hilary; Realism; Semantics (Philosophy); Réalisme.; Sémantique (Philosophie); PHILOSOPHY -- Movements -- Realism; PHILOSOPHY -- History & Surveys -- Modern; Realism; Semantics (Philosophy); Realismus; Electronic books; e-books.; Livres numériques.